Effects of reminiscence therapy on psychological outcome among older adults without obvious cognitive impairment: A systematic review and meta-analysis - Xu, Lijun; Li, Shasha; Yan, Renfu; Ni, Yingyuan; Wang, Yuecong; Li, Yue (Frontiers in Psychiatry, 2023)
Introduction: Reminiscence therapy has been a high-benefit and low-cost measure of psychosocial intervention for older adults in recent years. It has attracted much attention in the intervention study of older adults without obvious cognitive impairment. This study aimed to evaluate the effects of reminiscence therapy on psychosocial outcomes among older adults without obvious cognitive impairment and analyze the divergences of different intervention programs (form, duration, and setting) on outcomes. Methods: We searched the commonly used databases and used RevMan 5.4 in the meta-analysis (PROSPERO-ID: CRD42022315237). All eligible trials used the Cochrane Risk of Bias Tool and the Effective Public Health Practice Project quality assessment tool to identify the quality and determine the bias risk grade. Results: Twenty-seven studies were included, involving 1755 older adults. Meta-analysis showed that reminiscence therapy has a significant effect on both depression and life satisfaction. Group reminiscence played a significant role in improving life satisfaction. Depression symptoms were not affected by the intervention duration (P = 0.06), while life satisfaction was significantly improved after more than 8 weeks of intervention (P < 0.00001). Intervention settings drove differences in depressive symptoms (P = 0.02), and the effect size of the community was larger. Conclusion: Reminiscence therapy can significantly reduce depressive symptoms and improve life satisfaction. There are different effects of reminiscence therapy in different intervention schemes on psychological outcomes among older adults. More well-designed trials with large sample sizes and long-term follow-ups are necessary to confirm and expand the present results.